Numerical modelling of thermal waves via internal state variable approach - Bajer, Czesław; Kosiński, Witold (Computer Assisted Methods in Engineering and Science; Vol 2 No 4 (1995), 2023)
Numerical solutions by means of the space-time finite element method to initial-boundary value problems for a hyperbolic model of heat conduction, are obtained. The heat conduction description is based on a concept a rigid conductor with a scalar internal state variable, that leads to a modified Fourier law. The obtained results are compared with existing experimental data know for semi-conductor crystals at low temperature.